Canadians under fire : infantry effectiveness in the Second World War - Engen, Robert C. (Robert Charles) (McGill-Queen's University Press, 2009)
In Canadians Under Fire Robert Engen explores the dynamics of what combat looked like to Canada's infantrymen during the Second World War. Analyzing unexamined battle experience questionnaires from over 150 Canadian infantry officers, Engen argues for a reassessment of the tactical behaviour of Canadian soldiers in the Second World War. The evidence also shows that Marshall's theory of non-participation in combat by Allied forces is demonstrably false: Canadian soldiers took a continued and aggressive part in the fighting.